Implementasi Tanda Tangan Elektronik dalam Perjanjian - Lenggono, Roy Prabowo (KANJOLI Business Law Review, 2024)
Implementing electronic signatures has become a significant phenomenon and accelerated the adoption of digital technology in various sectors, including law and business. However, it also raises multiple current issues, such as data security, privacy, and the legal validity of electronically signed documents. This research aims to analyze the implementation of electronic signatures in agreements in Indonesia from a legal perspective and to identify the challenges and solutions needed to ensure the legitimacy and security of their use. This research uses a descriptive-analytical normative legal research method through a literature study. Implementing electronic signatures in agreements in Indonesia is an important step toward legal modernization. Therefore, intensive public education is needed to increase trust and acceptance of electronic signatures in every agreement.